Developing “Fill My Spirit” Application to Enrich English Grammar Ability of Tenth-Grade Students - Rosalia Vivi, Citra; Sari, Hesty Puspita; Aini, Miza Rahmatika (Konstruktivisme : Jurnal Pendidikan dan Pembelajaran, 2023)
This study aimed to establish the "Fill My Spirit" application as a learning media to enrich the grammar ability of tenth-grade students indSeniordHighdSchooldand to find out the effectiveness of the application as a learning media to enrich students’ grammar ability of tenth grade of Senior HighdSchool. Theddesigndindthisdresearch was research and development (RdanddD). The process of developing the application consisted of various stages, namely: (1) dThe Result of the research showed that 1) application model to enrich grammar skills in class X students, especially tenses that consisting of 2 tenses on the recount text consist of 2 tenses on recount text and completed with 3 guide books namely guide book for teacher, public and students;2) The developed application is valid proved by the result of the content English material validation (86%) and media validation (88%); and (3) Students and teachers gave positive responses toward reflected from the resulting questionnaire given 82% from students and 92% from teachers.